Analisis Pengendalian Biaya Operasional dalam Meningkatan Profitabilitass Perusahaan: Studi Kasus pada PT. Anugrah Maju Bersama Cemerlang Gambir DKI Jakarta - Arfa Alamsyah; Sulaeman Sulaeman; Iqbal Noor (AKUNTANSI 45, 2024)
This research aims to assess the effect of operational costs on profitability at PT Anugrah Maju Bersama Cemerlang, which is located in Gambir, DKI Jakarta. The method used is qualitative with an associative descriptive approach. The research results revealed that the company experienced a decrease in effectiveness in controlling operational costs, which had an impact on changes in profitability and caused losses. These findings highlight the importance of effective operational cost control to increase company profitability.